The best of brochure design 10 - Chua, Perry (Rockport Publishers, 2008)
Brochure design is a perennial in the world of marketing and graphic design, yet it can be challenging to execute successfully. This collection of brochure designs offers hundreds of ideas and advice for both professional graphic designers and students.